KEARIFAN LOKAL SEBAGAI RESOLUSI KONFLIK KEAGAMAAN - Wasisto Raharjo Jati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
This article aims to analyze the relation between local wisdom within religion conflicts resolution in post conflict divided society of Maluku. In the case of Maluku conflict religion was not core sources, but rivalry among societal element to compete for bureaucracy position and economic-politic resources. Religion is only becoming supporting conflict which provides moral legitimation and politic identity to strike others. The history of Maluku conflict indicated by subordination and domination relations that resulted discrimination and marginalization amidst society. The fallacy of the new order regime in 1999 can be said conflict escalation in Maluku that murdered million innocent peoples. Maluku conflict had resolved by Malino peace treaty in 2002 and 2003, however potency of conflict in grassroots can be reduced by local wisdom values. Pela gandong as local wisdom had a pivotal role in reconciliation process to recapitalize social capital which cracked during conflict. In addition to local wisdom, representation in bureaucracy also hold role player to reducing social gap between society elemental in Maluku.